2012
DOI: 10.1152/jn.00337.2012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identity, ontogeny, and cAMP modulation of the hyperpolarization-activated current in vestibular ganglion neurons

Abstract: Properties, developmental regulation, and cAMP modulation of the hyperpolarization-activated current (I(h)) were investigated by the whole cell patch-clamp technique in vestibular ganglion neurons of the rat at two postnatal stages (P7-10 and P25-28). In addition, by RT-PCR and immunohistochemistry the identity and distribution of hyperpolarization-activated and cyclic nucleotide-gated channel (HCN) isoforms that generate I(h) were investigated. I(h) current density was larger in P25-28 than P7-10 rats, increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(49 citation statements)
references
References 65 publications
12
37
0
Order By: Relevance
“…In the present study, we have shown a developmental increase in I h current density, a decrease in its activation time constant, and a positive shift of V 1/2 in VGCs obtained from P3 to P14 rats. These results are consistent with those of Almanza et al (2012), who compared properties of I h in VGCs obtained from rats between P7-10 and P25-28 (Almanza et al, 2012). In the present study, we also showed that the expression of HCN1 protein as well as its mRNA increases developmentally while the other HCN isoforms did not change during the same developmental period.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, we have shown a developmental increase in I h current density, a decrease in its activation time constant, and a positive shift of V 1/2 in VGCs obtained from P3 to P14 rats. These results are consistent with those of Almanza et al (2012), who compared properties of I h in VGCs obtained from rats between P7-10 and P25-28 (Almanza et al, 2012). In the present study, we also showed that the expression of HCN1 protein as well as its mRNA increases developmentally while the other HCN isoforms did not change during the same developmental period.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggest that HCN channels as well as Kv1 channels contribute to control the pattern of spike discharges in a complementary way. The HCN channel blocker ZD7288 changed the shape of APs, showing decrease in the AP spike height, increase in the AP spike width, decrease in the amplitude of AHP, and increase in the width of AHP, consistent with the results reported by Almanza et al (2012). The sculpting of APs is probably due to persistent activity of I h at the resting membrane potential since I h kinetics are considerably slower than those of the APs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations